(untitled) (Agora for Physical Education and Sport, 2018)
The aim of this paper was to find out the level of sportsmanship, enjoyment, motivation and attitude towards Physical Education by Secondary Education students. The sample consisted of 104 high school students (aged 15-18) of three different courses, to whom the Multidimensional Scale of Orientations to Sportsmanship, the Questionnaire of Attitudes towards Physical Education and the Measure of Enjoyment in Physical Activity Scale were administered. The results showed higher values related to interest and positive attitudes toward Physical Education among boys, and slightly higher in sportsmanship and enjoyment among girls. No significant differences were observed in any variables when related to students’ academic level. Enjoyment, positive attitude and motivation showed higher values among those involved in some kind of sport outside school hours. Finally, data showed that enjoyment seemed to be positively and significantly related to the students’ positive consideration of Physical Education and to their preference of this school subject.